2022
DOI: 10.3892/ol.2022.13328
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of parotid gland tumors at a single institution

Abstract: The aim of the present study was to analyze the clinical characteristics, surgical treatments and clinical outcome of patients with parotid gland tumors and to compare the results with those cited in the literature. A retrospective study was conducted in 140 patients (male, n=77; female, n=63) with parotid gland tumors who underwent parotidectomy at Hokuto Hospital Department of Otolaryngology-Head and Neck Surgery (Obihiro, Japan) between April 2007 and December 2021. Of the 140 patients enrolled, 118 (84.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
1
1
1
Order By: Relevance
“…We showed that age and sex are not independent risk factors for differentiating between benign and malignant parotid tumors. This finding was inconsistent with what has been reported previously 18,19,21 . One reason for the difference might be the small sample size, thus giving rise to the need for further analysis with a larger sample size.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…We showed that age and sex are not independent risk factors for differentiating between benign and malignant parotid tumors. This finding was inconsistent with what has been reported previously 18,19,21 . One reason for the difference might be the small sample size, thus giving rise to the need for further analysis with a larger sample size.…”
Section: Discussioncontrasting
confidence: 91%
“…This finding was inconsistent with what has been reported previously. 18,19,21 One reason for the difference might be the small sample size, thus giving rise to the need for further analysis with a larger sample size. To avoid overfitting, we divided parotid tumors, benign or malignant, into modeling and validation groups.…”
Section: Discussionmentioning
confidence: 99%
“…Mật độ u chủ yếu là chắc 74,3%, ranh giới rõ 97,1%, di động hạn chế 60%. Những biểu hiện này phù hợp với hầu hết các nghiên cứu trước đó [8], [9].…”
Section: đặC đIểm Lâm Sàngunclassified